Examination of the Postgraduate Theses Published on Amputee Football Players in the Field of Sports Sciences in Turkey - Kilinç, Zuhal; Karadağ, Haci; Kurt, Yusuf (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The aim of this research is to examine thesis published on amputee football players in the field of sports sciences in Turkey in terms of the level postgraduate, year of publication, purpose, age of participant, number of participant, data collection tools and results. Methods: In the literature, review studies are generally carried out with three different methods: systematic review, traditional review and meta-analysis. This research was designed using the systematic review method. A total of 17 theses were reached as a result of the search made by scanning the keywords "amputee and football amputee" between 20.01.2022 and 05.02.2022 on the database of the Turkish National Thesis Center. Results: Although there are very few postgraduate theses published in the field of physical education and sports sciences, it has been determined that there has been a great increase in recent years. At the same time, it was determined that the theses published were mostly master's theses. While the age range of the participant groups of these theses was not specified in some theses, it was determined that they were between the ages of 15-50 in other theses. The number of participant groups of theses varies considerably between theses. When examined in terms of data collection tool, it was determined that physical performance values were measured the most. Secondly, it was determined that the most measurement tool was questionnaire. It was determined that the least number of semi-structured interview forms were used. Conclusion: As a result, it has been determined that the number of postgraduate thesis researches on amputee football players in the field of physical education and sports is quite low and sports performance measurement tests are mostly applied in the existing theses. In future studies, it may be recommended to conduct studies examining psychological and social situations.